School Climate and Academic Achievement in Suburban Schools. (September 2016) - Sulak, Tracey N.
School climate research has indicated a relationship between the climate of a school and academic achievement. The majority of explanatory models have been developed in urban schools with less attention given to suburban schools. Due to the process of formation of suburban schools, there is a likelihood these campuses differ from the traditional urban school. The current study examined the predictive value of suburban school climate on academic achievement in a nationally representative sample of suburban campuses. The findings indicate behavior and racial/ethnic composition may impact achievement levels in suburban schools. The findings also indicate the location of the school and the surrounding crime may be a factor in suburban academic achievement.